Pengaruh Orientasi Pasar dan Kompetensi Sumberdaya Manusia Terhadap Loyalitas Pelanggan Melalui Kepuasaan Pelanggan - Ricky Indra Gunawan; Moeljadi Moeljadi; Siti Aisjah (Jurnal Manajemen dan Kewirausahaan, 2017)
The purpose of this research is to analyze the effect of market orientation and human resources competence to customer loyalty through customer satisfaction in Rumah Sakit Islam Malang. The analysis tool in this research is done using partial least square (PLS). The result shows that 1) market orientation has a significant impact towards customer loyalty, 2) human resource competency does not has direct significant impact towards customers loyalty, 3) market orientation has significant impact towards customers satisfaction, 4) human resource competency has a significant impact towards customer satisfaction, 5) market orientation and human resource competency has a significant impact toward customers loyalty through customers satisfaction https://doi.org/10.26905/jmdk.v5i1.1274